Clinical oncology module for the ESTRO core curriculum. (March 2021) - Benstead, Kim; Lara, Pedro C.; Eller, Yannick; Engell-Noerregaard, Lotte; Eriksen, Jesper G.; Gaye, Papa Macoumba; Jaal, Jana; Juretic, Antonio; Kase, Marju; Kouloulias, Vassilis; Kozma, Elvisa; Lagerlund, Magnus; et al.
Highlights: A clinical oncology module for the ESTRO core curriculum has been developed. It is based on CanMEDS 2015 containing 20 enabling competencies. Proficiency is defined by a range of Entrustable Professional Activities for each tumour site. Abstract: Introduction: Clinical oncologists are physicians with the competencies to manage cancer patients through the entire disease pathway combining the competencies of radiation and medical oncologists. The 4th edition of the European Society for Radiotherapy and Oncology Core Curriculum for Radiation Oncology/Radiotherapy (ESTRO curriculum) has received wide support by the clinical oncology community. The aim was to develop a clinical oncology module that could be combined with the ESTRO curriculum to enable clinical oncology trainees to follow a single curriculum. Materials and methods: A range of stakeholders including National Society representatives, an oncologist from a low- middle-income country, and a recently appointed specialist, developed and commented on iterations of the curriculum. Further modifications were made by the ESTRO Education Council. Results: The module is based on the CanMEDS 2015 framework and identifies 20 enabling competencies in the Medical Expert role that are required in addition to the ESTRO curriculum for the training of clinical oncologists. Recommendations are made for the levels of Entrustable Professional Activities (EPAs) to be attained by the end of training. Conclusions: The Clinical Oncology module, when combined with the ESTRO curriculum, covers the entire cancer pathway rather than being modality specific. It is hoped it will aid in the development of comparable standards of training in clinical oncology across Europe and may also have utility in low- and middle-income countries as well as providing a single curriculum for trainees.